School Choice, Youth Voice: How Diverse Student Policy Actors Experience High School Choice Policy. Issue 6 (September 2021) - Phillippo, Kate; Griffin, Briellen; Dotto, Bryan J. Del; Castro, David; Nagi, Ekram
School choice research is abundant, but rarely incorporates students' experiences or perspectives. This study investigates a diverse group of students' school choice experiences as they applied to, gained admission to and enrolled in high school in Chicago Public Schools, which offers over 130 options. Adapting Ball and colleagues' (2012) concept of policy actor positionality, we analyzed the role of students' developmental and social statuses in students' school choice experiences. Students' policy encounters were developmentally consistent, but their admissions results and subsequent academic trajectories diverged by their socioeconomic status. We discuss these findings' developmental and equity implications for school choice policy.